THE EFFECTIVENESS OF GUIDED IMAGERY ON DEPRESSION AND CORTISOL LEVELS IN COLON RECTAL CANCER PATIENTS - Saleh, Ariyanti; Syahrul Ningrat; Wa Ode Nurisna; Aulia Insani Latif (Jurnal Kesehatan, 2022)
Background: Depression in colon rectal cancer patients can inhibit the healing process, increasing the morbidity and mortality. Purpose of the study: This study aims to determine the effectiveness of guided imagery on the level of depression and cortisol. Guided imagery is a relaxation and comfort therapy that can provide a calm effect. Guided imagery is performed by guiding the patient in imagining a beautiful and comfortable place. Research Method: This study uses experimental design. The study sample consist of 52 patients with colon rectal cancer who undergo the treatment. Depression levels and examination of cortisol levels are carried out before and after the intervention. Guided imagery is given to 26 people in the intervention group, and 26 people in the control group for the standard care. Data analysis using independent t-test and dependent t-test if the data is normally distributed. Results: The use of Guided Imagery therapy can reduce the average level of depression in CRC patients but does not show changes in cortisol levels in patient’s body.